Phylogenetic analyses of rhizobia isolated from Aeschynomene spp. - EVI TRIANA (Biodiversitas Journal of Biological Diversity, 2005)
The 16S rDNA sequence of eleven strains isolated from nodules of Aeschynomene spp. have been determined and analyses together with sequence of other related taxa. Four bacterial groups were identified: (i) photosynthetic Bradyrhizobial group consist of IRBG2, IRBG228 dan IRBG 230; (ii) non-photosintetik Bradyrhizobium group consist of MAFF210127, MAFF210316, MAFF210318, dan MAFF210408; (iii) Rhodopseudomonas palustris group consist of HMD88, HMD89 dan 99D and (4) an isolate, 99C, that is related to Rhodopseudomonas acidophila. In addition, DNA-DNA hybridization was performed among HMD88, HMD89 and 99D strains. The result showed that DNA homology of HMD88, HMD89 and 99D with Rps. palustris were less than 30%, DNA homology of HMD88, HMD89 and Rps. Palustris with 99D is about or less than 20%, otherwise between HMD88 and HMD89, DNA similarity was more than 70%. The result suggest that HMD88 and HMD89 are the same species, meanwhile 99D is close related or different species in Rhodopseudomonas palustris group. Key words: 16S rDNA sequence, Aeshynomene sp., photosynthetic rhizobia, DNA-DNA hybridization, Rhodopseudomonas palustris